2022
DOI: 10.3389/fcvm.2022.884911
|View full text |Cite
|
Sign up to set email alerts
|

Pooled-Analysis of Association of Sievers Bicuspid Aortic Valve Morphology With New Permanent Pacemaker and Conduction Abnormalities After Transcatheter Aortic Valve Replacement

Abstract: BackgroundStudies on the association of Sievers bicuspid aortic valve (BAV) morphology with conduction disorders after transcatheter aortic valve replacement (TAVR) have not reached consensus.MethodsWe here performed a pooled-analysis to explore whether Sievers type 1 BAV morphology increased the risk of post-TAVR conduction abnormalities and permanent pacemaker implantation (PPI) compared to type 0. Systematic literature searches through EMBASE, Medline, and Cochrane databases were concluded on 1 December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…5,7 The same correlation exists for the LV end-diastolic volume or diameter. 6,16,24 Lastly, Zhang et al 25 concluded that patients with Sievers type 1 bicuspid aortic valve (BAV) morphology (presence of a raphe or fusion between the two leaflets) are more predisposed to PPI after TAVR, compared with patients with Sievers type 0 BAV morphology (absence of a raphe or fusion between the two leaflets).…”
Section: Anatomical Risk Factorsmentioning
confidence: 99%
“…5,7 The same correlation exists for the LV end-diastolic volume or diameter. 6,16,24 Lastly, Zhang et al 25 concluded that patients with Sievers type 1 bicuspid aortic valve (BAV) morphology (presence of a raphe or fusion between the two leaflets) are more predisposed to PPI after TAVR, compared with patients with Sievers type 0 BAV morphology (absence of a raphe or fusion between the two leaflets).…”
Section: Anatomical Risk Factorsmentioning
confidence: 99%